Physical activity and cognitive function in adults born very preterm or with very low birth weight-an individual participant data meta-analysis. - Kristina Anna Djupvik Aakvik; Silje Dahl Benum; Marjaana Tikanmäki; Petteri Hovi; Katri Räikkönen; Sarah L Harris; Lianne J Woodward; Brian A Darlow; Marit S Indredavik; Stian Lydersen; Paul Jarle Mork; Eero Kajantie; et al. (PLoS ONE)
Objective Individuals born very preterm (<32 weeks of gestation) or with very low birthweight (<1500g) have lower cognitive function compared with term-born peers. Furthermore, some studies suggest that they are less physically active as young adults than controls, but the relationship between physical activity and cognitive function remains unclear. We performed an individual participant data meta-analysis to examine whether being born preterm/with very low birth weight is associated with physical activity in adulthood and examined if cognitive function mediates this association. Study design Cohorts with data on physical activity and cognitive function in adults born very preterm/very low birth weight and term-born controls were recruited from the Research on European Children and Adults Born Preterm, and the Adults Born Preterm International Collaboration Consortia. A systematic literature search was performed in PubMed and Embase. Results Five cohorts with 1644 participants aged 22-28 years (595 very preterm/very low birth weight and 1049 controls) were included. Adults born very preterm/very low birth weight reported 1.11 (95% CI: 0.68 to 1.54) hours less moderate to vigorous physical activity per week than controls, adjusted for cohort, age and sex. The difference between individuals born very preterm/very low birth weight and controls was larger among women than among men. Neither intelligence quotient nor self-reported executive function mediated the association between very preterm/very low birth weight and moderate to vigorous physical activity. Results were essentially the same when we excluded individuals with neurosensory impairments. Conclusion Adults born very preterm/very low birth weight, especially women, reported less moderate to vigorous physical activity than their term-born peers. Cognitive function did not mediate this association. Considering the risk of adverse health outcomes among individuals born preterm, physical activity could be a target for intervention.